Association Between Hypernatremia and Delirium After Cardiac Surgery: A Nested Case-Control Study - Hong, Liang; Shen, Xiao; Shi, Qiankun; Song, Xiaochun; Chen, Lihai; Chen, Wenxiu; Chen, Shangyu; Xue, Yingyin; Zhang, Cui; Zhou, Jifang (Frontiers in Cardiovascular Medicine, 2022)
Background: The association between hypernatremia and delirium after cardiac surgery has rarely been investigated. This study aimed to determine whether hypernatremia increases the risk of delirium after exposure. Materials and Methods: From April 2016 to June 2021, 7831 consecutive patients receiving cardiac surgery were screened for potential enrollment. The primary outcome was post-operative delirium (POD). For the respective case of delirium, 10 controls were matched according to the index date within the nested case-control design. Hypernatremia exposure was defined as serum sodium > 145 mmol/L within 7 days before the index date. Generalized estimation equation was performed to assess excess risks for POD associated with hypernatremia, adjusted for demographics and clinical variables. Results: 7277 patients were included in the final analyses. 669 (9.2%) patients with POD were assigned to the case group, and 6690 controls were identified from the whole population. 66.5% of the cases and 36.3% of the controls had hypernatremia exposure. After being adjusted to certain well-recognized confounding factors, hypernatremia showed a significant correlation to increased risk of delirium after cardiac surgery (adjusted OR, 1.73; 95% CI, 1.41~2.12). E-value analysis suggested the robustness to unmeasured confounding. Conclusions: Hypernatremia was associated with increased risk of delirium after cardiac surgery. This finding could have implications for risk stratification, early detection and management of delirium in patients receiving cardiac surgery.